A forgotten war: World War I in the United States (Comillas Journal of International Relations, 2015)
This article aims to explain how and why the First World War became, and remains to this day, a forgotten war in the United States of America. It does so primarily through the lens of popular culture, examining forms of historical memory ranging from memorials and museums to Hollywood films and reenactment societies, though academic as well as popular writings are also touched on. The central premise is that while Americans wrote about and memorialised the Great War in stone and on film just as much as the rest of the Anglo-Saxon world in the inter-war decades, for the past seventy years the First World War in the USA has been eclipsed by the Second World War; a conflict much greater in scale and scope in terms of American involvement, especially in relation to military casualties. The ongoing competition for popular attention offered by the Civil War of the previous century is also noted, along with the ways in which the First World War tends to be approached in the classroom. Finally, the future prospects of World War I in American popular consciousness are examined in the context of the approaching centenary of USA entry into the conflict.
Keywords: AEF; films; museums; memorials; memory